Lactate-related metabolic reprogramming and immune regulation in colorectal cancer - Sun, Qianhui; Wu, Jingyuan; Zhu, Guanghui; Li, Tingting; Zhu, Xiaoyu; Ni, Baoyi; Xu, Bowen; Ma, Xinyi; Li, Jie (Frontiers in Endocrinology, 2023)
Changes in cellular metabolism involving fuel sources are well-known mechanisms of cancer cell differentiation in the context of carcinogenesis. Metabolic reprogramming is regulated by oncogenic signaling and transcriptional networks and has been identified as an essential component of malignant transformation. Hypoxic and acidified tumor microenvironment contributes mainly to the production of glycolytic products known as lactate. Mounting evidence suggests that lactate in the tumor microenvironment of colorectal cancer(CRC) contributes to cancer therapeutic resistance and metastasis. The contents related to the regulatory effects of lactate on metabolism, immune response, and intercellular communication in the tumor microenvironment of CRC are also constantly updated. Here we summarize the latest studies about the pleiotropic effects of lactate in CRC and the clinical value of targeting lactate metabolism as treatment. Different effects of lactate on various immune cell types, microenvironment characteristics, and pathophysiological processes have also emerged. Potential specific therapeutic targeting of CRC lactate metabolism is also discussed. With increased knowledge, effective druggable targets might be identified, with the aim of improving treatment outcomes by reducing chemoresistance.